Meridional motions of the afternoon radar aurora, auroral electrojets, and absorption patches under variable IMF conditions - R. A. Makarevitch (Annales Geophysicae, 2004)
The meridional motions of the CUTLASS HF and STARE VHF coherent echoes, IMAGE equivalent electrojet currents, and IRIS absorption patches during the postnoon/early-evening event of 14 February 2000 are presented. The motions were found to be synchronous, to a first approximation, for all instruments. The temporal correlation between motions in the radar and magnetometer data was exceptionally good, although spatially the areas with the E-region backscatter and most intense equivalent currents were not coincident, with the HF (VHF) echoes being shifted 100–200km (20–50km) equatorward (poleward). The meridional motions of the radar echoes and electrojet currents appeared to be controlled by the IMF Bz changes; the meridional propagation direction was equatorward (poleward) during the intervals when the IMF was southward (northward), with one exception when the poleward progression continued after the IMF southward turning. We relate the observed meridional motion patterns to the polar cap expansion/contraction during variable IMF conditions and discuss the relative importance of two types of processes: the dayside reconnection and IMF-triggered substorms. We also investigate the irregularity Doppler velocity for the STARE (144MHz) and CUTLASS (12MHz) observations at large flow angles in the context of the eastward and westward electrojet systems. We show that the 144-MHz Doppler velocity is determined by a combination of two factors: the sense of electrojet currents and the aspect angle conditions within the STARE field of view. Finally, the behavior of small dayside enhancements of the IRIS absorption (up to 0.5dB at 38.2MHz) accompanying the radar echoes and electrojet currents is examined. Since the velocity of the meridional displacements was close to that of the poleward/equatorward progressing intense currents, it is suggested that the absorption patches observed during the event were related to the heating of the E-region plasma by the unstable plasma waves in the regions of enhanced electric fields. Key words. Ionosphere (auroral ionosphere; electric fields and currents; plasma convection)